Cohesive zone modeling for mode I facesheet to core delamination of sandwich panels accounting for fiber bridging. (1st January 2018) - Höwer, Daniel; Lerch, Bradley A.; Bednarcyk, Brett A.; Pineda, Evan J.; Reese, Stefanie; Simon, Jaan-Willem
Abstract: A new cohesive zone traction-separation law, which includes the effects of fiber bridging, has been developed, implemented with a finite element (FE) model, and applied to simulate the delamination between the facesheet and core of a composite honeycomb sandwich panel. The proposed traction-separation law includes a standard initial cohesive component, which accounts for the initial interfacial stiffness and energy release rate, along with a new component to account for the fiber bridging contribution to the delamination process. Single Cantilever Beam tests on aluminum honeycomb sandwich panels with carbon fiber reinforced polymer facesheets were used to characterize and evaluate the new formulation and its finite element implementation. These tests, designed to evaluate the mode I toughness of the facesheet to core interface, exhibited significant fiber bridging and large crack process zones, giving rise to a concave downward/concave upward pre-peak shape in the load–displacement curve. Unlike standard cohesive formulations, the proposed formulation captures this observed shape, and its results have been shown to be in excellent quantitative agreement with experimental load–displacement results, representative of a payload fairing structure, as well as local strain fields measured with digital image correlation.